Facile synthesis of AgNPs on reduced graphene oxide for highly sensitive simultaneous detection of heavy metal ions. Issue 35 (18th April 2017) - Sang, Shengbo; Li, Dan; Zhang, Hui; Sun, Youyi; Jian, Aoqun; Zhang, Qiang; Zhang, Wendong
Abstract : Silver nanoparticles grown on reduced graphene oxide (AgNPs/RGO) were successfully synthesized via a facile in situ method. Abstract : Silver nanoparticles grown on reduced graphene oxide (AgNPs/RGO) were successfully synthesized via a facile in situ method. The samples were characterized by scanning electron microscopy (SEM), Raman spectroscopy, field emission transmission electron microscopy (FETEM) and X-ray diffraction (XRD). The results show that silver ions distribute extensively on the RGO sheets. In order to prepare an electrochemical sensor, the AgNPs/RGO nanocomposite was used to modify the surface of a magnetic glassy carbon electrode. The device was characterized by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The as-prepared AgNPs/RGO nanocomposite was measured with square wave anodic stripping voltammetry (SWASV), and exhibited excellent electrochemical activity and sensitivity towards the detection of heavy metal ions, including Pb(ii ), Cd(ii ), Cu(ii ) and Hg(ii ). The sensitivities were respectively 48.69, 40.06, 15.66 and 43.18 μA μM −1 and the limits of detection (LOD) were respectively 0.141, 0.254, 0.178 and 0.285 μM. Compared to the bare RGO film, the AgNPs/RGO nanocomposite showed a significantly higher activity for anodic stripping analysis of the four considered heavy metal ions; in particular, the peak current enhancement was about 1.5 times higher for Pb(ii ). Experiments also show that the AgNPs/RGO-modified electrode displays good anti-interference properties. Moreover, this study provides a potential material for electrochemical detection of heavy metal ions, individually or simultaneously.